2013
DOI: 10.1155/2013/925413
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Reconstruction for the Treatment of Musculoskeletal Tumors of the Upper Extremity

Abstract: In comparison with the lower extremity, there is relatively paucity literature reporting survival and clinical results of allograft reconstructions after excision of a bone tumor of the upper extremity. We analyze the survival of allograft reconstructions in the upper extremity and analyze the final functional score according to anatomical site and type of reconstruction. A consecutive series of 70 allograft reconstruction in the upper limb with a mean followup of 5 years was analyzed, 38 osteoarticular allogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 20 publications
5
41
0
1
Order By: Relevance
“…Therefore, amputation of the shoulder girdle should be avoided if possible. 3 The increasing and often unpredictable longevity of patients with metastatic disease, 1,4 coupled with higherthan-expected failure rates after internal fixation with or without intralesional treatment and radiotherapy, 5,6 has led to renewed interest in more aggressive local control efforts through proximal humeral resection and reconstruction. 7 Reconstruction of the defects that result after resection of the proximal humerus could be performed by different comparable methods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, amputation of the shoulder girdle should be avoided if possible. 3 The increasing and often unpredictable longevity of patients with metastatic disease, 1,4 coupled with higherthan-expected failure rates after internal fixation with or without intralesional treatment and radiotherapy, 5,6 has led to renewed interest in more aggressive local control efforts through proximal humeral resection and reconstruction. 7 Reconstruction of the defects that result after resection of the proximal humerus could be performed by different comparable methods.…”
Section: Introductionmentioning
confidence: 99%
“…The complication rate at 5 years was 25 % with 1 patient with local recurrence, 1 with infection, and 2 with non-unions. The MSTS functional score demonstrated comparable results with osteoarticular allografts, 25 and 23 points, respectively [19].…”
Section: Clinical Outcomesmentioning
confidence: 78%
“…Aponte-Tinao et al [19] reported in 2013 their experience using osteoarticular allografts in different locations of the upper extremity. Twenty-one patients of these series had reconstructions of the proximal humerus.…”
Section: Historymentioning
confidence: 99%
See 2 more Smart Citations